2022
DOI: 10.3390/v14112367
|View full text |Cite
|
Sign up to set email alerts
|

Infection with SARS-CoV-2 Variants Is Associated with Different Long COVID Phenotypes

Abstract: COVID-19 has been associated with a broad range of long-term sequelae, commonly referred to as “long-COVID” or “post-COVID-19” syndrome. Despite an increasing body of literature, long COVID remains poorly characterized. We retrospectively analysed data from electronic medical records of patients admitted to the post-COVID-19 outpatient service of the Infectious and Tropical Diseases Unit, Careggi University Hospital, Florence, Italy, between June 2020 and June 2021, 4–12 weeks after hospital discharge. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…A second interesting finding is that the variant wave is associated with Long COVID symptoms even with adjustment for timing of vaccination (preinfection, postinfection, or not vaccinated) and number of symptoms during acute infection; more recent variants were associated with lower odds of Long COVID. One prior study suggested that there may be some subtle differences in Long COVID symptoms by variant wave (more dyspnea with ancestral strain, more neuropsychiatric and myalgic symptoms with Alpha, and hair loss with Delta for example) [ 23 , 24 ]. Our findings are consistent with 3 prior studies that suggested that there may be a lower prevalence of Long COVID with the more recent variant waves (Epsilon, Omicron) [ 15 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A second interesting finding is that the variant wave is associated with Long COVID symptoms even with adjustment for timing of vaccination (preinfection, postinfection, or not vaccinated) and number of symptoms during acute infection; more recent variants were associated with lower odds of Long COVID. One prior study suggested that there may be some subtle differences in Long COVID symptoms by variant wave (more dyspnea with ancestral strain, more neuropsychiatric and myalgic symptoms with Alpha, and hair loss with Delta for example) [ 23 , 24 ]. Our findings are consistent with 3 prior studies that suggested that there may be a lower prevalence of Long COVID with the more recent variant waves (Epsilon, Omicron) [ 15 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, among more than 600 children and adolescents previously hospitalised due to COVID-19 in Argentina, risk factors for long COVID, with headache, cough, and fatigue comprising the most common symptoms, included older age apart from symptomatic infection and comorbidities, including diabetes [37]. In an Italian cohort of 428 patients, assessed 4-12 weeks after hospital discharge, it was found that female sex and severe SARS-CoV-2 infection were the main risk factors for post-COVID manifestations, among which chronic dyspnoea and fatigue were the most common [38]. Finally, a recent Czech study examining healthcare workers at least 12 weeks after the onset of SARS-CoV-2 infection, revealed that female sex and increasing age were the only significant predictors of post-COVID syndrome, with almost half of those patients reporting fatigue interfering with their daily life [39].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence has shown CVD PACS symptoms in patients infected by the Wuhan original strain. For example, Palpitation and tachycardia were reported in patients infected with the Wuhan variant in the cohorts from Spain and Italy [54, 55]. In U.S., long-term CVD sequelae was early reported from a cohort in Michigan (6 March to 1 July 2020) [56] and a cohort of veterans (1 March 2020 to 15 January 2021) [20].…”
Section: Discussionmentioning
confidence: 99%